Associations between metabolic disorders and Sjögren's disease - Chihiro Iwaya; Junichi Iwata (Elsevier, 2024)
Sjögren's disease (SjD) is a systemic autoimmune disorder characterized by dry eyes and mouth caused by chronic inflammation and is often accompanied by various extra-glandular manifestations, including fatigue and diffuse pain. Although the pathogenesis of the disease remains elusive, several factors (e.g. environmental, genetic and hormonal factors, abnormal metabolic status) are associated with this condition. Accumulating evidence suggests a potential role of cholesterol metabolism in immune and non-immune modulation in various diseases. In this review, we summarize the current findings on the associations between cholesterol metabolism and SjD.